2000
DOI: 10.1002/1521-3749(200008)626:8<1837::aid-zaac1837>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Neue Phosphaniminato-Komplexe von Molybdän und Wolfram. Die Kristallstrukturen von [(μ-S2N2){MoCl4(NPPh3)}2], [Mo(NPPh3)4][BF4]2, [W(S)2(NPPh3)2] und [Ph3PNH2]+[SCN]

Abstract: Professor Dietrich Babel zum 70. Geburtstag gewidmet Inhaltsu È bersicht. Der zweikernige Molybda Èn(V)-Phosphaniminato-Komplex [(l-S 2 N 2 ){Mo V Cl 4 (NPPh 3 )} 2 ] (1) wird durch Reaktion des Chlorthionitren-Komplexes [Mo VI Cl 4 (NSCl)] 2 mit Me 3 SiNPPh 3 in Dichlormethan als olivgru È ne Kristalle erhalten. Die Messung der magnetischen Suszeptibilita Èt im Temperaturbereich von 2±30 K zeigt fu È r 1 ideales Curie-Verhalten mit einem magnetischen Moment von 1,60 B.M. pro Molybda È natom. Nach der Kristall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The reduction of S 2 N 2 was investigated by a combined cyclic voltammetry (CV) and EPR study, which revealed that this species is initially reduced to give the dimeric radical anion [S 4 N 4 ] •– , followed by decomposition into [S 3 N 3 ] − . The formation of group 6 phosphoraniminato complexes of S 2 N 2 (e.g., [(μ-S 2 N 2 )­MCl 4 (NPPh 3 ) 2 ] (M = Mo and W; 927 and 928 ) was reported by Dehnicke and co-workers …”
Section: Inorganic Rings Derived From Group 12–17 Elementsmentioning
confidence: 83%
“…The reduction of S 2 N 2 was investigated by a combined cyclic voltammetry (CV) and EPR study, which revealed that this species is initially reduced to give the dimeric radical anion [S 4 N 4 ] •– , followed by decomposition into [S 3 N 3 ] − . The formation of group 6 phosphoraniminato complexes of S 2 N 2 (e.g., [(μ-S 2 N 2 )­MCl 4 (NPPh 3 ) 2 ] (M = Mo and W; 927 and 928 ) was reported by Dehnicke and co-workers …”
Section: Inorganic Rings Derived From Group 12–17 Elementsmentioning
confidence: 83%